Performance effects of internal pre- and per-cooling across different exercise and environmental conditions: A systematic review - Roriz, Maria; Brito, Pedro; Teixeira, Filipe J.; Brito, João; Teixeira, Vitor Hugo (Frontiers in Nutrition, 2022)
Exercise in a hot and humid environment may endanger athlete´s health and affect physical performance. This systematic review aimed to examine whether internal administration of ice, cold beverages or menthol solutions may be beneficial for physical performance when exercising in different environmental conditions and sports backgrounds. A systematic search was performed in PubMed, Web of Science, Scopus and SPORTDiscus databases, from inception to April 2022, to identify studies meeting the following inclusion criteria: healthy male and female physically active individuals or athletes (aged ≥ 18 years); an intervention consisting in the internal administration (i.e., ingestion or mouth rinse) of ice slush, ice slurry or crushed ice and/or cold beverages and/or menthol solutions before and/or during exercise; a randomized crossover design with a control or placebo condition; the report of at least one physical performance outcome; and to be written in English. Our search retrieved 2714 articles in total; after selection, 43 studies were considered, including 472 participants, 408 men and 64 women, aged 18-42 years, with a VO2max ranging from 46.2 to 67.2 mL∙kg -1∙min-1. Average ambient temperature and relative humidity during the exercise tasks were 32.4 ± 3.5°C (ranging from 22°C to 38°C) and 50.8 ± 13.4% (varying from 20.0% to 80.0%), respectively. Across the 43 studies, 7 exclusively included a menthol solution mouth rinse, 30 exclusively involved ice slurry/ice slush/crushed ice/cold beverages intake, and 6 examined both the effect of thermal and non-thermal internal techniques in the same protocol. Rinsing a menthol solution (0.01%) improved physical performance during continuous endurance exercise in the heat. Conversely, the ingestion of ice or cold beverages did not seem to consistently increase performance, being more likely to improve performance in continuous endurance exercises, especially when consumed during exercises. Co-administration of menthol with or within ice beverages seems to exert a synergistic effect by improving physical performance. Even in environmental conditions that are not extreme, internal cooling strategies may have an ergogenic effect. Further studies exploring both intermittent and outdoor exercise protocols, involving elite male and female athletes and performed under not extreme environmental conditions are warranted.